WESTERN KAZAKHSTAN IN THE CONTEXT OF ETHNIC DEPORTATIONS FROM THE NORTH CAUCASUS - Sundetova, Akmaral Nagasbaevna; Beknazarov, Rahym Agibaevic; Hazretali, Tursun Mahanovic (History, Archeology and Ethnography of the Caucasus, 2026)
This article examines the deportation of North Caucasian peoples within the USSR to Western Kazakhstan during the Great Patriotic War, focusing on their social status and subsequent adaptation. The study investigates the resettlement and living conditions of “special settlers” within the Aktobe, West Kazakhstan, and Guryev regions. The research utilizes content analysis of contemporary publications on ethnic deportations from both the Republic of Kazakhstan and the Russian Federation, supplemented by European scholarship on the subject. The authors analyzed documents from local archives in Western Kazakhstan, cross-referencing them with materials from the primary central archives of Russia and Kazakhstan, as well as publicly available online data from the German Federal Military Archive. The analysis revealed significant discrepancies between regional and central archival records regarding the total number of special settlers, their geographic distribution, and their employment status in Western Kazakhstan. Additionally, the authors introduce previously unpublished materials transferred from regional departments of the Ministry of Internal Affairs (UMVD) to regional archival funds. The study concludes that the majority of special settlers in Western Kazakhstan were concentrated in the Aktobe region, while the remainder were stationed at the “Kazakhstanneftestroy” construction project in the Guryev region under the direct supervision of the NKVD. The identification of substantial gaps and contradictions in the accounting of North Caucasian special settlers highlights a significant opportunity for further research into the mechanisms of regional deportation policy.
Keywords: ethnic deportation; special settlers; Western Kazakhstan; North Caucasus; Chechen people; social conditions